UTILIZATION OF AREN (Arenga pinnata Merr.) SAWMILLING WASTE FOR EDIBLE MUSHROOM CULTIVATION MEDIA - Djarwanto Djarwanto; Sihati Suprapti (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2016)
Aren (Arenga pinnata Merr.) is a multipurpose tree that can be utilized for palm sugar, alcoholic drinks, beverages and construction wood. The use of aren sawdust has not been studied intensively. This study examines the utilization of aren sawdust as cultivation media for edible mushrooms. Aren sawdust was mixed with rice bran, CaCO3, gypsum, fertilizers and distilled water before sterilization in 30 minutes pressurized autoclave at 1210C and 1.5atm. The mixed media was inoculated with pure cultures containing four mushrooms species (Pleurotus flabellatus, P. ostreatus, P. sajor-caju and Lentinula edodes) and incubated for five weeks to allow mycelium growth producing fruit bodies. The fruit bodies were harvested everyday within four months and examined for its gained mushroom-weight and biological conversion efficiency/BE. The core part of aren trunk was cut into smaller pieces of 10 cm (width) by 5 cm (thickness), by 120 cm (length). Each core sample was bored from the surface inward, creating holes with a particular distance apart. Each hole was inoculated with pure cultures containing 6 mushroom species (four species above, P. cystidiosus and Auricularia polytricha). The inoculated samples were slanted on bamboo support, and placed in a bamboo hut. Harvesting was carried out everyday after the fruiting body became mature and examined for its gained mushroom weight. Results show that the use of sawdust supplemented with nutritious material is more likely to improve the mushroom yield than that of aren sawn-timber core. In this case, the BE values with aren-sawdust media were 21.97-89.45% (P. flabellatus), 15.36-105.36% (P. ostreatus), 63.88-76.86% (P. sajor-caju), and up to 62.88% (L. edodes). Meanwhile, the yields (gained mushroom weight) with aren sawn-timber media were 210g (P. ostreatus), 368g (P. flabellatus), 331g (P. sajor-caju) and 48g (A. polytricha); however, P. cystidiosus and L. edodes inoculated on aren stem core failed to grow.